Adult-Onset Ligneous Conjunctivitis with Detection of a Novel Plasminogen Gene Mutation and Anti-Plasminogen IgA Antibody: A Clinicopathologic Study and Review of Literature. (1st November 2016) - Tu, Yufei; Gonzalez-Gronow, Mario; Kolomeyer, Anton M.; Cohen, Alice; Pruzon, Joanna; Milman, Tatyana; Chu, David S.
Abstract: Purpose : To report a novel plasminogen gene mutation and detection of anti-plasminogen antibodies in a patient with ligneous conjunctivitis successfully treated with 60% fresh frozen plasma (FFP). Methods : Retrospective data collected on a 45-year-old Caucasian female presenting with unilateral chronic membranous lesions. Results : Laboratory investigation demonstrated decreased plasminogen antigen level, plasminogen activity, and rate of plasminogen activation by u-PA or t-PA, and elevated plasminogen activator inhibitor-1. Anti-plasminogen IgG and IgA antibodies were detected. DNA analysis revealed a novel Asp432Asn heterozygous missense mutation in the plasminogen gene (exon 11). The patient was treated with topical 60% FFP, achieved complete remission after four months, and remained membrane-free for over five years of follow-up. Conclusions : A novel plasminogen gene mutation, deficiency of plasminogen antigen and activity, and anti-plasminogen IgG and IgA antibodies were identified in a patient with adult-onset ligneous conjunctivitis. Sixty percent FFP maintained this patient disease-free for over five years.